Peran Hukum Dalam Percepatan Pembangunan Ekonomi - sanusi, sanusi (Universitas Pancasakti Tegal, 2021)
The purpose of this study is to examine the relationship between law and economics, not a one-way relationship but a reciprocal and mutually influencing relationship. In fact, it is often said that the legal relationship with the economy is like two sides of a coin that cannot enter and complement each other. The role of law in economic development can be briefly interpreted as an effort to increase per capita income continuously and gradually. The research method uses the type of library research, normative juridical research approach, data sources from secondary data and qualitative data analysis. The results show that the economic order must be instrumental in overcoming the problems that exist in every economic society, namely economic functions, economic activities and economic order that lead to a policy. Economic law is needed as a driver to balance the increase in economic activity so that its implementation does not violate the interests of the general public. The role of law in development has a more comprehensive and basic meaning than the term legal development or legal reform. Legal development refers more to efficiency, in the sense of increasing legal efficiency.